KLAUSUL NON-KOMPETISI DALAM PERJANJIAN KERJA DIKAITKAN DENGAN PRINSIP KERAHASIAAN PERUSAHAAN DALAM PERSPEKTIF HAK UNTUK MEMILIH PEKERJAAN BERDASARKAN HUKUM POSITIF INDONESIA - Sudjana, Sudjana (Jurnal Al-Amwal, 2018)
An employment agreement which includes a non-competition clause is created by the company for the purpose of protecting its business secrets. In practice, however, this clause limits workers' rights and is contrary to Indonesia's positive law. The purpose of the study determines the principle of confidentiality with regard to the right to choose an occupation under Indonesian positive law and to formulate protection for workers in the case of inclusion of non-competition clauses related to corporate secrecy in the perspective of the right to choose an occupation.This research was conducted by using normative juridical approach by reviewing the literature,that is using secondary data in law scope through studying literature. This research is an analytical descriptive research, which be used to understand the reality that happened in field that is related to Indonesian positive law. The research results showed that. First, an employment agreement in which there is a non-competition clause, has infringed a man's right specifically the right to freedom to choose an ocuupation which protected and guaranteed by the state as stated in the Law on Human Rights and the Employment,so this kind of clause still causing a dilemma because on the one hand the company has an interest in trade secrets and other material interests, whereas workers have the right of freedom to choose a job.Second, Protection to workers related to their rights in choosing a job has been granted by the state. It is contained in Article 38 paragraph (2) of the Human Rights Law and the Employment Law.